Bluetooth and WLAN coexistence challenges and solutions. - Golmie, N.
In this article we discuss solutions to the interference problem caused by the proximity and simultaneous operation of Bluetooth and WLAN networks. We consider different techniques that attempt to avoid time and frequency collisions of WLAN and Bluetooth transmissions. We conduct a comparative analysis of their performance, and discuss the trends and trade-offs they bring for different applications and interference levels. Performance is measured in terms of packet loss, TCP goodput, delay, and delay jitter.
Keywords: Bluetooth; TCP goodput; Adaptive frequency hopping mechanism; Delay jitter; Interference aware scheduling; Interference estimation; Interference problem; Local area network; Packet loss; Transport control protocols; Wireless LAN